A Human Antibody that Binds to the γ-carboxyglutamic Acid Domain of Factor IX Is a Potent Antithrombotic In Vivo - Refino, Canio J.; Himber, Jacques; Burcklen, Louis; Moran, Paul; Peek, Mark; Suggett, Shelley; Devaux, Brigitte; Kirchhofer, Daniel (Thrombosis and Haemostasis, 1999)
10C12, a human antibody F(ab’)2, which specifically binds to the Gla domain of factor IX, interfered with all known coagulation processes that involve factor IX/IXa. These include the function of the intrinsic Xase complex and the activation of zymogen factor IX by factor XIa and by the tissue factor:factor VIIa complex. Furthermore, 10C12 potently inhibited activated partial thromboplastin clotting times (APTT) in plasma of guinea pig and rat, thus enabling in-vivo evaluation. In guinea pigs, a bolus administration of 10C12 (10 μg/kg) prevented cyclic flow variations in damaged carotid arteries without affecting coagulation or bleeding parameters. At a 100-fold higher dose, 10C12 had no effect on normal hemostasis as assessed by the cuticle bleeding time. At this dose, 10C12 was also efficacious in a rat arterial thrombosis model, substantially reducing clot weight and duration of vessel occlusion while prolonging ex-vivo APTT only 1.2-fold. The dose of heparin required to produce comparable antithrombotic effects prolonged the APTT by 12-fold and increased the tail bleeding time (TBT) by 8-fold. In contrast, 10C12 had no effect on TBT. However, rat tails showed a tendency for rebleeding which 10C12 exacerbated. In conclusion, the antithrombotic potency of the 10C12 antibody in two species provides evidence for an important role of F.IX, and its Gla domain in particular, during thrombogenesis under arterial flow conditions. The relative safety at effective doses of this fully human antibody suggests that it may have therapeutic value for treatment of thrombotic disorders.AbbreviationsGla: γ-carboxyglutamic acid; CDRs: complementarity determining regions; CVFs: cyclic flow variations; TF:F.VIIa: tissue factor:factor VIIa; APTT: activated partial thromboplastin time; PT: prothrombin time; ACT: whole blood activated clotting time; CBT: cuticle bleeding time; TBT: tail bleeding time